Interferometric Analysis of RADARSAT Strip-Map Mode Data - Geudtner, Dirk; Vachon, Paris; Mattar, Karim; Schättler, Birgit; Gray, A.L. (2001)
RADARSAT’2 synthetic aperture radar (SAR) provides several strip-map and ScanSAR beam modes. We consider the interferometric analysis of RADARSAT SAR strip-map mode data sets, which differ in several respects from the well-known ERS SAR version. Interferometric image pairs with suitable baselines can be selected through evaluation of the projected equatorial satellite ground track drift. We acquired several data sets with useful interferometric baselines over Bathurst Island, Canada. This Arctic study site provides dry and barren surface conditions, reducing the effects of temporal decorrelation over RADARSAT’s 24-day repeat-pass interval, especially during the winter time, allowing generation of useful interferograms and demonstration of interferometry techniques. The effects of RADARSAT’s imaging geometry on the azimuth and range frequency spectra are analyzed to establish their influence on spectral alignment. This also includes a discussion of the rotational decorrelation caused by skewed orbit geometry. For three image pairs, we compare the relative accuracy of RADARSAT’s annotated and external definitive orbit ephemeris data and discuss the merits of the two types of orbit data for determination of the three-dimensional interfereometric imaging geometry.